1) 1-b²=(1-b)(1+b)
-b²=-1
b=1; -1
2)(a-12)(a+12)=a²-144
а²=144
а=12; -12
3)(4x⅛)=½x
4)(0,3a+0,9в)=0,09а²+0,54ав+0,81в²
1)с²-0,25=0
(с-0,5)(с+0,5)=0
или
с²=0,25
с=корень из 0,25 ; корень из -0,25
с=0,5; -0,5
2)х²-1=(х-1)(х+1)
х²=1
х=-1; 1
3)(12-а)(12+а)=144-а²
-а²=-144
4)(3а+⅓в)²=9а²+2ав+1/9в²
1) 1-b²=(1-b)(1+b)
-b²=-1
b=1; -1
2)(a-12)(a+12)=a²-144
а²=144
а=12; -12
3)(4x⅛)=½x
4)(0,3a+0,9в)=0,09а²+0,54ав+0,81в²
1)с²-0,25=0
(с-0,5)(с+0,5)=0
или
с²=0,25
с=корень из 0,25 ; корень из -0,25
с=0,5; -0,5
2)х²-1=(х-1)(х+1)
х²=1
х=-1; 1
3)(12-а)(12+а)=144-а²
-а²=-144
а=12; -12
4)(3а+⅓в)²=9а²+2ав+1/9в²